KONSIDERASI UNTUK MENERAPKAN STUDENT GROUPING DALAM PEMBELAJARAN TATA BAHASA TOEFL DENGAN MENGGUNAKAN APLIKASI NST TOEFL EXPLORER - Barotun Mabaroh; Diah Anita Pusparini (Jurnal Bahasa Lingua Scientia, 2018)
Lecturers must consider many things before implementing strategies in the learning process. This is because learning strategies also affect students’ learning outcomes. Once, low-achiever students can improve their competence because of the working strategies. Contrarily, high-achiever students may get decreased because of the worst strategies. From various strategies in the learning process, student grouping is a popular strategy which supports collaboration among students. Yet, the lecturer must be able to consider several things related to student grouping. The main consideration is “with whom” and “how” students should be grouped. "With whom" covers appropriate decision on grouping students  homogeneously or heterogeneously. Whereas "how" is interpreted as how many students should be gathered in every group. The decision of both must be based on logical reasoning in accordance with the learning context. To answer these two aspects, the research team analyzed data which were previously collected by using observation, questionnaire, interview, and documentation. This research was carried out throughout Grammar TOEFL learning process using NST TOEFL Explorer, in English Education Study Program of STKIP PGRI Pasuruan. The result confirmed that student grouping in this context was done more appropriately by grouping heterogeneous students with five members. This grouping strategy is able to show an improvement in students’ learning outcomes in grammar TOEFL mastery.